IMPLEMENTASI KARAKTER GOTONG ROYONG BERBASIS ONLINE COLLABORATIVE LEARNING - Listyaningsih Listyaningsih (PROCEEDING UMSURABAYA, 2022)
Gotong royong for the Indonesian people is one of the local wisdoms or local wisdom because gotong royong is a characteristic of the Indonesian people that distinguishes other nations. Gotong royong is a national character whose values are inherited from ancestors and these values have been embedded in the soul and have become the personality of the Indonesian nation since ancient times. In terms of solving the problems experienced by the Indonesian people, gotong royong is an alternative to overcome the problems that occur. Gotong royong at this time is not only interpreted in the form of community service, but is also interpreted in a broad sense, for example mutual cooperation in learning. In essence, humans are social beings who need other people in their lives. As social beings, humans need to help others who are experiencing difficulties. Learning based on the values of local wisdom, namely the value of mutual cooperation is very important to be instilled in all students. The implementation of the gotong royong character based on online collaborative learning can be applied to all subjects through activities carried out in groups, working together, sharing, and helping each other with fellow group members.Â Keywords: character; mutual cooperation; online collaborative learning